Student opinions on the escalation of violence in Israel and Gaza and antisemitism at German universities - Thomas Hinz; Anna Marczuk; Frank Multrus (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Hamas's attack on Israel and the subsequent military response, the number of antisemitic incidents in Germany has risen significantly - including at universities, according to many reports. The media report on anti-Israeli sentiments, and Jewish students are threatened and attacked. Funded by the Federal Ministry of Education and Research (BMBF), the Research Group on Higher Education at the University of Konstanz conducted a survey among students in December 2023 to assess the current climate of opinion on the war in Israel and the Gaza Strip, the willingness to protest in Germany, the perception of antisemitism in society and at universities and, finally, antisemitic attitudes among students. Over 2,000 students enrolled at German universities in the winter semester 2023/24 took part. The findings can be compared with the results of a population survey conducted at the same time.
urn:nbn:de:bsz:352-2-rg7tb902gh9g8
Keywords: 320; Politischer Konflikt; Antisemitismus; Hochschule; Studierende; Meinung; Deutschland; Gazastreifen; Israel